On the control of vibrations using synchrophasing - Dench, M. R.; Brennan, M. J. [UNESP]; Ferguson, N. S. (Elsevier, 2013)
This paper describes the application of a technique, known as synchrophasing, to the control of machinery vibration. It is applicable to machinery installations, in which several synchronous machines, such as those driven by electrical motors, are fitted to an isolated common structure known as a machinery raft. To reduce the vibration transmitted to the host structure to which the machinery raft is attached, the phase of the electrical supply to the motors is adjusted so that the net transmitted force to the host structure is minimised. It is shown that while this is relatively simple for an installation consisting of two machines, it is more complicated for installations in which there are more than two machines, because of the interaction between the forces generated by each machine. The development of a synchrophasing scheme, which has been applied to propeller aircraft, and is known as Propeller Signature Theory (PST) is discussed. It is shown both theoretically and experimentally, that this is an efficient way of controlling the phase of multiple machines. It is also shown that synchrophasing is a worthwhile vibration control technique, which has the potential to suppress vibration transmitted to the host structure by up to 20 dB at certain frequencies. Although the principle of synchronisation has been demonstrated on a one-dimensional structure, it is believed that this captures the key features of the approach. However, it should be realised that the mode-shapes of a machinery raft may be more complex than that of a one-dimensional structure and this may need to be taken into account in a real application. © 2013 Elsevier Ltd.
Keywords: Common structures; Control of vibrations; Electrical motors; Electrical supply; One-dimensional structure; Real applications; Suppress vibration; Synchronous machine; Propellers; Synchronous motors; Installation